Key features of observational research data preparation for evidence synthesis - A. A. Lazarev; K. V. Sapozhnikov; D. G. Tolkacheva; N. A. Sableva (Реальная клиническая практика: данные и доказательства)
Relevance. Observational studies (OS) play a key role in the healthcare system because they provide real-world data (RWD). Unlike randomized controlled trials (RCTs), such studies better reflect routine medical practice. This makes them especially valuable for decision-making aimed at improving the quality and accessibility of medical care.The objective of this article was to analyze key points related to OS data preparation derived from RWD for further evidence synthesis. This work was conducted within a review of asymptomatic hyperuricemia (AH) and was intended to lead to the consensus among rheumatologists on the management patterns of patients with AH in the Russian Federation.Materials and methods. This article examined and described the process of preparing OS data for evidence synthesis.Results. The data analysis revealed significant measures of the efficacy and safety of the medical interventions and pivotal aspects of preparing OS data for subsequent evidence synthesis. We employed a number of techniques to overcome discrepancies in the presentation of the included OS data, including subgroup pooling, unloading of mean and standard deviations from medians and quartiles, and the synthesis of mean values in quartiles from a lognormal distribution via multiple replications. Urinary acid levels based on available OS were calculated using the Hunter-Schmidt estimator. Changes in glomerular filtration rate (GFR) across quartiles were pooled in accordance with the sequential Cochrane community approach or recalculated using community delta unloading equations in instances where GFR values fell within the observation time boundaries.Findings. The results confirmed the importance of preparing appropriate OS data for evidence synthesis. OS provides valuable data for practical use when considering clinical factors and evaluating long-term treatment outcomes.Conclusions. Consequently, observational studies and their preparations can provide a more comprehensive and precise understanding of the efficacy of medical interventions and enhance the quality and accessibility of care for all patients.